Is a periglacial biota responsible for enhanced dielectric response in basal ice from the Greenland Ice Core Project ice core? - Tison, Jean-Louis; Souchez, Roland; Wolff, Eric W.; Moore, John; Legrand, Michel R.; De Angelis, Martine (1998)
A detailed dielectric profiling (DEP) conductivity profile (σ∞) measured in the 6 m of the basal silty ice sequence from the Greenland Ice Core Project (GRIP) ice core (Summit, Central Greenland) is presented and compared to previous multi-parametric studies. DEP conductivities span the whole glacial-interglacial range observed higher up in the GRIP core (9-25 μS m-1). Values in the bottom meter of the sequence reach the level of some of the highest peaks from Holocene volcanic layers in the core (33 μS m-1). On a steady increase of the σ∞ values down the sequence are superimposed large fluctuations "inphase" with other variables measured in the core such as δ18O, debris content, or gas compositions in CO2 and CH4. Analysis of the type and strength of intercorrelations shows that the controlling variable for the DEP signal must be closely related to the gas content and composition of the ice. Plausible candidates for this causality link are investigated. Enhancing of the σ conductivity by CO2 and CH4 encaged in the ice lattice as gas hydrates is ruled out since these are nonpolar clathrates of structure I, known as having negligible impact on the orientational stability of the water molecules under ac currents. NH4+ is proposed as the best candidate since it has been shown to enhance DEP conductivities by introducing Bjerrum defects in the ice lattice and since it could have been initially present partly as gaseous NH3 in the ice. This proposition is supported by the NH4+ profile in the basal ice sequence. Using calibration curves from higher up in the core, it is shown that σ is in fact fully explained by intracrystalline conductivity of pure ice solely disrupted by ammonium impurities in the ice lattice. The origin of the NH4+ signal is discussed in the light of organic acid profiles (formate, acetate, and oxalate). It appears that the most likely source is local degradation of biological residues, which supports the hypothesis that part of the basal ice was formed locally, in the absence of the present-day ...